The impact of empathy, sensation seeking, anxiety, uncertainty, and mindfulness on the intercultural communication in China during the COVID-19 - Nadeem, Muhammad Umar; Kulich, Steve J.; Zabrodskaja, Anastassia; Bokhari, Ijaz Hussain (Frontiers in Public Health, 2023)
Objective: The study seeks to explore factors that have shaped intercultural communication effectiveness (ICE) of international students (IS) during the COVID-19 pandemic. The theoretical predictions of anxiety uncertainty management (AUM) are considered to assess ICE of the IS who stayed in China through COVID-19 pandemic. The prime causal factors of AUM theory (anxiety, uncertainty, and mindfulness) are included with empathy and sensation seeking in examining their impact on ICE among IS in China. Method: A quantitative research design was designed to survey IS via convenience samples from across China with a total of 261 IS from 42 different cultural backgrounds responded to invitations to participate in a Chinese-English survey. The well-established measurement tools were adopted to measure empathy (Cultural Empathy scale), sensation seeking (Brief Sensation Seeking Scale), anxiety (Intercultural Anxiety scale), uncertainty (Intercultural Uncertainty scale), mindfulness (Cognitive and Affective Mindfulness Scale-Revised), and ICE (Perceived Effectiveness of Communication scale). Findings: The findings revealed that anxiety (t = -3.61, p < .05) and uncertainty (t = -2.51, p < .05) had a negative impact on ICE. However, mindfulness (t = 3.93, p < .05), empathy (t = 3.60, p < .05), and sensation seeking (t = 7.93, p < .05) had a positive influence on ICE. Furthermore, the moderating effect of mindfulness is affirmed in this study. Conclusion: The study has reconfirmed the theoretical reasonings and applicability of AUM theory with the addition of empathy and sensation seeking by the IS on the cultural context of China during the COVID-19 pandemic.